Harnessing community musicians as living archives for “sustainable” teaching and learning of Ugandan musics at Makerere University - Makwa, Dominic D. B. (International Library of African Music, 2025)
At the Department of Performing Arts and Film at Makerere University, Kampala, Uganda, there is a growing trend of integrating community musicians into music and dance education through workshops on Ugandan musical traditions. These musicians, who play a vital role in the creation, preservation, and transmission of traditional music, function as living archives within their communities. Drawing on research conducted at Makerere University from 2021 to 2023, this article examines how engaging community musicians as key contributors to teaching and learning Ugandan musics has the potential to decolonise music education in Uganda. In describing the benefits of this inclusive approach, I critique the persistence of elitist frameworks in Ugandan university music and dance departments, which often prioritise engagement with PhD holders and published materials over community-based knowledge. I argue that community musicians, as living archives, offer invaluable insights that can foster the sustainable teaching and learning of Uganda’s diverse musical heritage. Sustainable teaching and learning, as conceptualised in this article, involve educational practices that acknowledge and integrate the contributions of all stakeholders in the production, dissemination, and appreciation of knowledge, thereby ultimately benefiting educational institutions, students, and the communities to which students may return after graduation.
Keywords: Musicians; Decolonisation; Archives; Education; Decolonial Music Education; Community-based Music Knowledge; Western Music Knowledge Frameworks; Community Musicians; Living Archives; Uganda; African Music; Music Education